Reducing the Risks of Environmental Pollution by Agents of Biological Origin - VALIULLIN, L. R.; MUKHAMMADIEV, R. S.; SOLOVYOVA, A. S.; SKVORTSOV, E. V.; MUKHAMMADIEV, Rin. S.; VALIULLINA, D. A.; KASANOVA, N. R. (Journal of Environmental Management and Tourism, 2020)
The neutralizing ability of the mycotoxin zearalenone with the KPM-2 biological preparation was studied. Changes in the cytotoxic properties and biochemical parameters of cell cultures under the influence of zearalenone on the background of the use of the drug KPM-2 were studied. As a result of the conducted studies, it is clear that the cytotoxicity of zearalenone in the minimum dose did not differ from the control and at the maximum dose of 3*10 -3 M, cell death was higher by 75% in comparison with the control. When using the drug KPM-2 in a concentration of 2*10 -9 CFU/ml, the cytotoxicity of zearalenone decreased only by 44.9% in comparison with the control. When zearalenone was exposed to cell culture at a dose of 3*10 -3 M, the activity of the enzyme alanine aminotransferase (ALT) increased by 51.7% compared to the control group, and when using the drug KPM-2 at a concentration of 2*10 -9 CFU/ml, ALT activity was higher than control by only 32.1%, respectively. The activity of aspartate aminotransferase (AST) in the group with a concentration of zearalenone 3*10 -3 M increased by 53.9% compared to the control group, when using the drug KPM-2, the neutralization of the toxic effect of zearalenone was observed and the AST index increased by only 44.0%. The concentration of lactic acid when exposed to zearalenone at a dose of 3 * 10 -3 M decreased by 26.1%, and in the group after neutralization of zearalenone with KPM-2 in a concentration of 2*10 -9 CFU/ml, the decrease in this indicator was only 16% compared to the control. The concentration of lactic acid when exposed to zearalenone at a dose of 3 * 10 -3 M decreased by 26.1%, and in the group after neutralization of zearalenone with KPM-2 in a concentration of 2*10 -9 CFU/ml, the decrease in this indicator was only 16% compared to the control. It is proposed to use the drug KPM-2 in the form of a suspension, which has the ability to neutralize the mycotoxin zearalenone and reduce the toxic effect on living organizations.